Penyuluhan Pemberdayaan Limbah Cair Aren Untuk Pembuatan Nata de Legen di Desa Gebang, Pesawaran, Lampung - Tundjung Tripeni Handayani; Sutyarso; Emantis Rosa; Lucy Adi Tama; R. Fadly Bayu Dwiyoga; ENDANG NURCAHYANI (CV. Multi Kreasi Media, 2022)
Society in general, has long known the palm tree (Arenga pinnata Merr.) as a tree that can produce materials for the craft industry. Almost all parts or products of this plant can be utilized and have economic value, however, this plant has received less attention to be developed or cultivated seriously by various parties. Most of the farmers only process the palm sugar into brown sugar and fro, while the sap water is only made for ordinary drinks. The selling price of palm sap is also very cheap, especially at harvest time the price drops sharply. Based on these reasons, it is necessary to develop new innovations in the processing of palm sap which has only been used as an ordinary drink. The new innovation is to make nira as Nata de Legen as an alternative to Nata de Coco. Through this innovation, it is hoped that the people of Gebang Village, Pesawaran, Lampung will know more about the other benefits of palm sap as a high-value food. This counseling is also expected to be able to increase public insight to utilize palm sap into products that have added value economically.